The Floats Of Grice's Conversational Maxims In "1001 Jokes" Humor Book By Richard Wiseman - Chadafi, Muamar, Agus Wijayanto, Ph.D, Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This study focuses on analyzing the floats of Grice's conversational maxims in "1001 Jokes" humor book. This study is aimed (1) to describe types of Grice's conversational maxims are frequently floated in "1001 Jokes" humor book, (2)to describe the implicature found in "1001 Jokes" humor book, and (3) to describe the maxim floats lead to funny jokes in"1001 Jokes" humor book. The writer employs descriptive qualitative approach to reach and to conclude the research findings in this study. In collecting data the writer uses documentation method, and to analyze data the writer refers to Grice's cooperative principle theory. Based on 30 data analyzed in this study obtained from "1001 Jokes" humor book, the writer found that (1)21 of the data or 70% float maxim of quality, 4 of data or 13.33% float maxim of manner, 3 of the data or 10% float maxim of quantity, 1 of the data or 3.33% floats maxim of relevance, and 1 of the data or 3.33% floats all maxims. Then, from the implicature the researcher found that (2) scalar implicature is to show contrast meanings between an utterance to other one, generalized conversational implicature is to explain the utterances used in the "1001 Jokes" humor book that do not need a special context to have humorous meaning, particularized conversational implicature is to demonstrate the utterances needing a specific context to have humorous meanings, and scalar implicature is to describe the joke utterances that have degree of meaning. Afterwards, the researcher found that (3) there are two aspects making the maxim floats lead to funny jokes in"1001 Jokes" humor book, i.e., relief, and incongruity of the word or the lexis. Besides that the writer also found that the floats of all maxims make a strong surprising meaning of the joke utterances increasing the degree of funny.